Simpanan deposito mudharabah dan tingkat bagi hasil Deposito berpengaruh pada kinerja keuangan bank syariah - Tiastiti, Septianing (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This study aims to determine the effect of mudharabah deposit deposits and deposit profit sharingrates on financial performance at Islamic commercial banks. This study uses secondary datasources in the form of quarterly financial bank documentation of Islamic commercial banks. Theresults of the study based on the t-test or partially show that mudharabah deposits have a positiveand significant effect on the financial performance of sharia commercial banks and the depositsharing rate has a positive and no significant impact on financial performance. Simultaneously(F test) shows that mudharabah deposit and deposit sharing rates have a positive and significanteffect on financial performance.